2021
DOI: 10.18553/jmcp.2021.27.3.367
|View full text |Cite
|
Sign up to set email alerts
|

Burden of illness among patients with dementia-related psychosis

Abstract: Depending on dementia type and disease progression, approximately 20%-70% of patients experience dementia-related psychosis (DRP), characterized by hallucinations and/or delusions resulting in worse clinical outcomes and greater caregiver burden compared with patients without DRP. OBJECTIVE: To compare real-world clinical events, health care resource utilization (HCRU), and health care costs among matched cohorts of DRP versus dementiaonly patients. METHODS: This retrospective database analysis examined commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 43 publications
3
7
0
Order By: Relevance
“…In a study of patients with probable Alzheimer’s disease, patients with a high Neuropsychiatric Inventory (NPI) score (i.e., more severe NPS) had formal and total direct costs USD 3000 to USD 6000 and USD 10,500 to USD 16,000 higher than patients with a low NPI score, and a one-point increase in NPI score was associated with an annual increase in total direct costs of USD 250 to USD 400 [ 5 ]. Our findings are also consistent with a recent report that patients with dementia-related psychosis were more likely to have diagnoses for behavioral health conditions and experience clinical events, and, consistently, had higher mean all-cause and dementia-related HCRU, relative to those with dementia only [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…In a study of patients with probable Alzheimer’s disease, patients with a high Neuropsychiatric Inventory (NPI) score (i.e., more severe NPS) had formal and total direct costs USD 3000 to USD 6000 and USD 10,500 to USD 16,000 higher than patients with a low NPI score, and a one-point increase in NPI score was associated with an annual increase in total direct costs of USD 250 to USD 400 [ 5 ]. Our findings are also consistent with a recent report that patients with dementia-related psychosis were more likely to have diagnoses for behavioral health conditions and experience clinical events, and, consistently, had higher mean all-cause and dementia-related HCRU, relative to those with dementia only [ 27 ].…”
Section: Discussionsupporting
confidence: 92%
“…Recent studies have reported that compared with older adults with dementia without psychosis, those with psychosis have more clinical events, such as falls and fractures, higher health care utilization, and higher mortality rates [7,11]. Given that dementia is composed of various dementia types, each with its own underlying etiology and disease trajectory, this current study describes the similarities and differences across the dementia types in the incidence of clinical events and treatment patterns after patients with dementia are diagnosed with psychosis.…”
Section: Discussionmentioning
confidence: 92%
“…Recent studies have reported that compared with older adults with dementia without psychosis, those with dementia-related psychosis have more serious risks, including falls and fractures, higher healthcare utilization, and higher mortality rates [7,17]. Specifically, the authors of a prior study conducted using Medicare claims from 2008 to 2016 found that patients with dementia-related psychosis had a hazard ratio of 2.4 (95% confidence interval [CI], 2.3-2.4) to enter in longterm care and a mortality hazard ratio of 2.1 (95% CI, 2.0-2.1) compared with those with dementia without psychosis [7].…”
Section: Open Accessmentioning
confidence: 99%
“…Specifically, the authors of a prior study conducted using Medicare claims from 2008 to 2016 found that patients with dementia-related psychosis had a hazard ratio of 2.4 (95% confidence interval [CI], 2.3-2.4) to enter in longterm care and a mortality hazard ratio of 2.1 (95% CI, 2.0-2.1) compared with those with dementia without psychosis [7]. Another study of patients with dementia who received commercial insurance or Medicare Advantage with Part D benefits during 2008 to 2018 found that a higher proportion of patients with psychosis experienced falls/fractures (psychosis group, 28%; no psychosis group, 14%) or cardiovascular effects (psychosis group, 7%; no psychosis group, 4%) compared with patients without psychosis [17].…”
Section: Open Accessmentioning
confidence: 99%